Hybrid film of single-layer graphene and carbon nanotube as transparent conductive electrode for organic light emitting diode - Kumar, P. (Elsevier Ltd, 2019)
Single layer graphene as a transparent conductive electrode (TCE) suffers from high sheet resistance, low work function, and hydrophobicity. In this work, a hybrid TCE of single-layer graphene, carbon nanotube (CNT) and gold nanoparticles (Au NP) decoration is proposed. The hybridization of graphene with CNT enhances the electrical conductivity while maintaining its high transmittance. The Au NP decorated TCE shows a sheet resistance of â¼100 Î©/sq and transmittance of 96. The potential of TCE is demonstrated in a solution-processed yellow organic light emitting diode (OLED). By introducing a thin layer of Al-doped zinc oxide between the Au NPs and graphene-carbon nanotube networks which increases the hydrophilicity of the surface, OLED with a current efficiency of â¼2.1 cd/A and a turn-on voltage of â¼5 V is obtained suggesting that this TCE can be a viable option for OLED-anode. Â© 2019 Elsevier B.V.